CNT-PDMS foams as self-powered humidity sensors based on triboelectric nanogenerators driven by finger tapping - Mohaddeseh Vafaiee; Faezeh Ejehi; Raheleh Mohammadpour (Scientific Reports, 2023)
Abstract An increasing number of frequently applied portable electronics has raised the significance of self-powered systems. In this regard, triboelectric nanogenerators (TENGs) have drawn considerable attention due to their diversity of design and high power output. As a widely used material in TENG electrodes, polydimethylsiloxane (PDMS) shows attractive characteristics, such as electron affinity, flexibility, and facile fabrication. To achieve active TENG-based humidity sensing, we proposed a straightforward method to enhance the hydrophilicity of PDMS by two parallel approaches: 1. Porosity induction, 2. Carbon nanotube (CNT) compositing. Both of the mentioned processes have been performed by water addition during the synthesis procedure, which is not only totally safe (in contrast with the similar foaming/compositing routes), but also applicable for a wide range of nanomaterials. Applying the modified electrode as a single-electrode TENG-based humidity sensor, demonstrated an impressive enhancement of sensing response from 56% up to 108%, compared to the bare electrodes. Moreover, the detecting range of ambient humidity was broadened to higher values of 80% in a linear behavior. The fabricated humidity sensor based on a CNT-PDMS foam not only provides superior sensing characteristics but also is satisfactory for portable applications, due to being lightweight and desirably self-powered.